2016
DOI: 10.1177/0961203316660202
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Argentine version of Lupus Quality of Life questionnaire

Abstract: The Argentine version of LupusQoL is a valid, reliable and reproducible instrument to assess quality of life. In this study, cut-off points that allow the classification of patients regarding whether they have good or bad quality of life are established for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Furthermore, a cohort study of 182 French patients with SLE showed that the French version of LupusQoL was significantly lower only for physical health, pain, and intimate relationship in patients with SLEDAI >4 [ 30 ]. Conversely, no significant differences in any domains of an Argentine version of LupusQoL were observed between 147 patients with a SLEDAI score of <4 and ≥4 [ 31 ]. The heterogeneity of the findings from the abovementioned studies might be explained by differences in ethnic composition, cultural setting, and healthcare infrastructure, which could affect the perception of HRQoL in patients with SLE [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a cohort study of 182 French patients with SLE showed that the French version of LupusQoL was significantly lower only for physical health, pain, and intimate relationship in patients with SLEDAI >4 [ 30 ]. Conversely, no significant differences in any domains of an Argentine version of LupusQoL were observed between 147 patients with a SLEDAI score of <4 and ≥4 [ 31 ]. The heterogeneity of the findings from the abovementioned studies might be explained by differences in ethnic composition, cultural setting, and healthcare infrastructure, which could affect the perception of HRQoL in patients with SLE [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively, in Argentina, LupusQoL was associated neither with disease activity nor with damage. 18…”
Section: Introductionmentioning
confidence: 99%
“…Comparatively, in Argentina, LupusQoL was associated neither with disease activity nor with damage. 18 Research regarding the factors associated with HRQoL in Latin American patients with SLE remains limited. In order to address this knowledge gap toward the goal of improving management and care, we conducted this study in order to define factors associated with HRQoL in predominantly Mestizo patients with SLE using a disease-specific tool for HRQoL (LupusQoL).…”
Section: Introductionmentioning
confidence: 99%
“…It has been adapted and validated in different languages including Spanish. 21 It contains 34 items grouped into eight domains: physical health, pain, planning, intimate relationships, burden to others, emotional health, body image, and fatigue. The total score ranges from 0 (worst QoL) to 100 (best QoL).…”
Section: Slaqmentioning
confidence: 99%